Oxygen Consumption of Litopenaeus vannamei in Intensive Ponds Based on the Dynamic Modeling System - Abdul Wafi; Heri Ariadi; Abdul Muqsith; Mohammad Mahmudi; Mohammad Fadjar (Journal of Aquaculture and Fish Health, 2021)
In intensive shrimp culture, oxygen consumption of shrimp is an important indicator that greatly affects the physiological condition of shrimp as a reared organism. The purpose of this study was to dynamically determine the oxygen consumption of shrimp in intensive culture as well as the variables of water quality and shrimp growth. This research was conducted with the concept of ex-post facto causal design in intensive aquaculture ponds during the shrimp cultivation period. During the shrimp culture period, the rate of oxygen consumption of shrimp is inversely related with the  sigmodial average increase in shrimp body weight. Meanwhile, based on the simulation analysis with the dynamic modeling concept, it is shown that oxygen consumption was linear to the dynamics of  average daily gain and inversely proportional with the increasing rate of shrimp biomass in the ponds. In addition, oxygen consumption rate of shrimp in intensive ponds had a close relationship with water salinity and total organic matter. In conclusion, dynamically, the fluctuation of oxygen consumption rate and average daily gain of shrimp in intensive culture are closely related to the stability of the water quality conditions on the shrimp habitat.